2008
DOI: 10.1029/2007jc004270
|View full text |Cite
|
Sign up to set email alerts
|

Thin sea ice thickness as inferred from passive microwave and in situ observations

Abstract: [1] Microwave radiometric signals from sea ice strongly reflect physical conditions of a layer near the ice surface. This study examines the extent to which the relationships of thickness with brightness temperature and with emissivity hold for thin sea ice, approximately <0.2-0.3 m, and how those relationships may arise from changes in brine characteristics through modification of dielectric properties near the ice surface. In order to address these questions we made concurrent measurements of sea ice thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 34 publications
0
34
0
1
Order By: Relevance
“…For sea ice, this can be explained in part on the desalination of the ice as the ice becomes thicker [9]. A fairly robust measurement used to determine the ice thickness is the polarization ratio, which can be interpreted as a normalized difference between the horizontally and vertically polarized emissions at a given frequency.…”
Section: B Calculation Of Ice Thickness From Passive Microwave Datamentioning
confidence: 99%
See 1 more Smart Citation
“…For sea ice, this can be explained in part on the desalination of the ice as the ice becomes thicker [9]. A fairly robust measurement used to determine the ice thickness is the polarization ratio, which can be interpreted as a normalized difference between the horizontally and vertically polarized emissions at a given frequency.…”
Section: B Calculation Of Ice Thickness From Passive Microwave Datamentioning
confidence: 99%
“…Methods have been presented in the literature to calculate the sea-ice thickness from various sensors [9]- [12]. Estimates of sea-ice thickness can be calculated at a resolution of approximately 1 km using data from visible/infrared (VIS/IR) sensors [11], with the limitation that this source of data cannot be used during cloudy conditions.…”
mentioning
confidence: 99%
“…The thin ice thickness retrieval algorithms are linear or exponential regression equations between polarization ratios (PR) or the V-to H-polarization ratios (R) and AVHRR or Moderate Resolution Imaging Spectroradiometer (MODIS) thicknesses. Naoki et al (2008) suggested that the observed decrease of near ice surface salinity as a function of ice thickness, which results in the modification of the ice dielectric properties and further ice emission (i.e., brightness temperatures), is the main reason for the observed relationship between brightness temperature and ice thickness. In addition, the relationship between brightness temperature and ice thickness is more pronounced for H-polarization and for a lower frequency (e.g., 10.7 GHz).…”
Section: Introductionmentioning
confidence: 99%
“…Weather forecasts near ice-covered regions are significantly improved when the accurate information regarding the ice state is available [2]. Sea ice thickness can be estimated using the data from passive microwave and visual/infrared (VIS/IR) sensors [3], [4] and radar and laser altimetry [5], [6]. Estimates from VIS/IR sensors are of particular interest because these sensors typically provide global coverage on a daily basis, at a relatively fine resolution ( ).…”
Section: Introductionmentioning
confidence: 99%